2020
DOI: 10.1177/2050312120974167
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with incidence of depressiveness among the middle-aged and older Estonian population

Abstract: Objective: Relatively scant research among older Estonian population describes factors associated with the incidence of depressive symptoms. This study identifies factors associated with the incidence of depressiveness among middle-aged and older Estonians over 2- and 4-year periods. Method: In this cross-sectional analysis, logistic regression models are used to identify the factors associated with the incidence of depressiveness over 2- and 4-year periods. The data were drawn from the Survey of Health, Agein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Four longitudinal studies (9-11) involving 14,604 participants were included in the involuntary retirement and depression meta-analysis. Three studies (9,11) showed a significant association between involuntary retirement and depression; while the other one study (10) indicated no relation between them. The pooled RR of overall data was 1.31 (95% CI, 1.13-1.51; P = 0) for the unexpectedly retired vs. employed, with low heterogeneity (I 2 = 37.7 %, P heterogeneity = 0.186) (Figure 2).…”
Section: Involuntary Retirement and Depressionmentioning
confidence: 92%
See 4 more Smart Citations
“…Four longitudinal studies (9-11) involving 14,604 participants were included in the involuntary retirement and depression meta-analysis. Three studies (9,11) showed a significant association between involuntary retirement and depression; while the other one study (10) indicated no relation between them. The pooled RR of overall data was 1.31 (95% CI, 1.13-1.51; P = 0) for the unexpectedly retired vs. employed, with low heterogeneity (I 2 = 37.7 %, P heterogeneity = 0.186) (Figure 2).…”
Section: Involuntary Retirement and Depressionmentioning
confidence: 92%
“…One article included participant already taking antidepressants or having hospital treatment for depression, one article included men living with HIV, two articles using the same population, nine cross-sectional designed articles, and 129 articles without multivariate-adjusted RRs/ORs concerning the relation between involuntary retirement and depression were excluded. Thus, 10 longitudinal studies from eight articles (5)(6)(7)(8)(9)(10)(11)(12) were included in the analysis (Table 1).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations